Hippocampal Interaction With Area 25, but not Area 32, Regulates Marmoset Approach–Avoidance Behavior. (23rd February 2019) - Wallis, Chloe U; Cockcroft, Gemma J; Cardinal, Rudolf N; Roberts, Angela C; Clarke, Hannah F
Abstract: Affective disorders are associated with increased sensitivity to negative feedback that influences approach–avoidance decision making. Although neuroimaging studies of these disorders reveal dysregulation in primate cingulate areas 25 and 32 and the anterior hippocampus (aHipp), the causal involvement of these structures and their interaction in the primate brain is unknown. We therefore investigated the effects of localized pharmacological manipulations of areas 25 and 32 and/or the aHipp of the marmoset monkey on performance of an anxiolytic-sensitive instrumental decision-making task in which an approach–avoidance conflict is created by pairing a response with reward and punishment. During control infusions animals avoided punishment, but this bias was reduced by increasing glutamate release within the aHipp or area 32, and inactivation or 5-HT1a antagonism within area 25. Conversely, increasing glutamate release in area 25 enhanced punishment avoidance but, in contrast to previous reports, area 32 and aHipp inactivations had no effect. Simultaneous inactivation or 5-HT1a antagonism within area 25, but not area 32, abolished the reduced punishment avoidance seen after increasing aHipp glutamate. Besides providing causal evidence that these primate areas differentially regulate negative feedback sensitivity, this study links the decision-making deficits in affective disorders to aberrant aHipp–area 25 circuit activity.